Nest Building and Bird Behavior - Collias, Nicholas E. (Nicholas Elias), 1914-2010 (Book collections on Project MUSE., 1984)
This book is a comprehensive study of nest-building behavior in birds. A much-needed synthesis of the previously scattered literature on this central aspect of avian biology, it is organized by behavior problems and focuses on evolution as its unifying theme. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.